ANALISIS WACANA KRITIS SARA MILLS TERHADAP REPRESENTASI GENDER DALAM IKLAN PRODUK RUMAH TANGGA DI YOUTUBE - Suprayitno, Ari; Irwansyah, Ramadani; Syafitra, Dina; Turiyah, Turiyah; Hermawan, Dedi; Nur, Siti Habibah (Program Studi Pendidikan Bahasa Indonesia FKIP-UNIVA Medan, 2024)
This study aims to uncover gender bias in household product advertisements through critical discourse analysis, focusing on the ‘SOS New Sereh Floor Cleaner’ advertisement aired on YouTube on October 25, 2017. YouTube as an increasingly dominant digital marketing platform offers advertisers the opportunity to reach a wider audience at an efficient cost. However, the advertisements aired also risk reinforcing gender stereotypes, especially in the representation of women’s roles as housekeepers. Using a qualitative approach with Sara Mills’ critical discourse theory, this study aims to analyze how language, visuals, and symbols in advertisements shape unequal gender narratives. The results of the analysis show that the advertisements tend to place women in positions that are closely connected to domestic activities, reinforcing traditional gender roles that can influence social perceptions of women’s roles in public spaces. This study is expected to provide deeper insight into the impact of digital advertising in shaping social discourse related to gender, as well as provide recommendations to advertisers to create fairer and more equal representation in the world of advertising.